It clearly says subtraction:
x + 3y = 2 ..... (1)
-x + y = 1 ..... (2)
(2) * -1 ----> x - y = -1 ..... (3)
Subtract (3) from (1),
x - x + 3y -(-y) = 2 - (-1)
4y = 3
y = 3/4
Put y = 3/4 in (2)
-x + 3/4 = 1
-x = 1 - 3/4
x = 3/4 - 1
x = -1/4
x = -1/4, y = 3/4
2007-07-15 00:22:56
·
answer #1
·
answered by Akilesh - Internet Undertaker 7
·
1⤊
0⤋
x+3y=2
-x+y=1
subtract the first two equation gives
2x=1 divide the equation throught by 2 gives
x=1/2
then substitute the value of x=1/2 in the first equation
1/2+3y=2 multiply the equatin by 2
1+6y=4
and add -1 both side of the equality
6y=3
devide equation through out by 6
y=3/6=1/2
answer: x=1/2=0.5
y=1/2=0.5
2007-07-16 11:32:03
·
answer #2
·
answered by shijil k 1
·
0⤊
1⤋
The subtraction method I believe is when you simply add or subtract one equation from another so you get one of the variables alone. In this case, you would add so the x and -x cancel out. So...
x + 3y = 2
-x + y = 1
----------------
4y = 3
----------------
y = 3/4
Next, substitute to find x.
-x + y = 1
becomes
-x + 3/4 = 1
----------------
-x = 1/4
----------------
x = -1/4
Your answers are:
x= -1/4
y= 3/4
2007-07-14 11:27:14
·
answer #3
·
answered by Anonymous
·
0⤊
1⤋
x + 3y = 2
-x + y = 1
y= 1+x
x + 3(1+x) = 2
x + 3 + 3x =2
4x = 2-3
4x = -1
x= -1/4
y= 1-1/4
y= 4/4 - 1/4
y= 3/4
(-1/4,3/4)
2007-07-16 12:32:09
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
x + 3y = 2
-x + y = 1
y= 1+x
x + 3(1+x) = 2
x + 3 + 3x =2
4x = 2-3
4x = -1
x= -1/4
y= 1-1/4
y= 4/4 - 1/4
y= 3/4
(-1/4,3/4)
2007-07-14 10:51:04
·
answer #5
·
answered by fofo m 3
·
0⤊
1⤋